1985
DOI: 10.1111/j.1600-0765.1985.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 3H‐Methyltrienolone (3H‐R1881) to androgen receptors in human gingiva

Abstract: Binding of 3H‐Methyltrienolone (3H‐R1881) to cytoplasmic androgen receptor protein and its translocation into nuclei in human gingiva was demonstrated. 3H‐R1881 binds to androgen receptors with high affinity (Kd= 1.7−1.9 × 10−9 M) and low capacity (10–16 fmol/mg protein). The binding was specific for DHT binding sites and was destroyed by proteolytic enzymes (pronase and trypsin). These results suggest that 3H‐R1881 can be used as a ligand in combination with nonradioactive DHT to study androgen receptors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Three of those studies detected ER (9, 10, 12) but none offered information on the intracellular distribution or on cellular individuality. There have been several immunohistochemical studies on ER examined on normal or pathological oral tissues (13)(14)(15)(16)(17)(18)(19), and three of them also carried out progesterone receptor (PR) staining (15)(16)(17). Four of seven reported that they succeeded in observing ER positive reactions in some subjects (15,(17)(18)(19), and one for PR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Three of those studies detected ER (9, 10, 12) but none offered information on the intracellular distribution or on cellular individuality. There have been several immunohistochemical studies on ER examined on normal or pathological oral tissues (13)(14)(15)(16)(17)(18)(19), and three of them also carried out progesterone receptor (PR) staining (15)(16)(17). Four of seven reported that they succeeded in observing ER positive reactions in some subjects (15,(17)(18)(19), and one for PR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Preferential accumulation and retention of hormones may occur depending upon the number of cytoplasmic and nuclear receptors that bind to particular hormones within the tissue. Many investigations have reported the preferential localization and retention of sex steroids, for example, estrogens [97,98], androgens [98] and progestins [99] in periodontal tissues as well [90,100]. The presence of specific hormonal receptors determines the response and regulates gene expression regarding the specific hormone ligand [101].…”
Section: Periodontium As a Target Tissue For Sex Steroid Hormonesmentioning
confidence: 99%
“…Almost all work on the tissue localization of sex steroid hormones in the periodontium was accomplished in the late 20th century and has been reviewed in detail (107). In summary, these studies have revealed that estrogens (7, 33, 198), androgens (197) and progestins (117, 205) were preferentially localized and retained in periodontal tissues (28), which was determined by the expression of specific steroid hormone receptors.…”
Section: Evidence For the Periodontium As A Target Tissue For Sex Stementioning
confidence: 99%
“…In the periodontium, the majority of our understanding of hormone action has accumulated from preliminary observations during the late 20th century. For periodontal tissues, intracellular binding proteins have been partially characterized for estrogens (81, 126, 178, 198), androgens (175, 197) and progesterone (196). The human gingival cytosol receptor for estrogen is a high‐affinity ( K d ≈ 340 ƒM), low‐capacity (≈ 4.5 ƒmol/mg of protein), heat and proteolytic enzyme‐sensitive protein that exhibits steroid specificity of binding to estradiol but not to cortisol, progesterone or testosterone (198).…”
Section: Evidence For the Periodontium As A Target Tissue For Sex Stementioning
confidence: 99%